UPAYA WORLD TRADE ORGANIZATION (WTO) DALAM MENGATASI SENGKETA DAGANG KERTAS A4 ANTARA INDONESIA DAN AUSTRALIA (2017-2019) - Lia Anggraini; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study discusses the dispute settlement process between the two countries through dispute settlement body WTO. World Trade Organization (WTO) is a global international organization that specifically regulates issues in trade between countries. WTO itself replaces the role of GATT 1947 as an international trade institution. In 2017, Australia declared that Indonesia had dumped A4 paper which is exported to its country. Indonesian government is accused of providing subsidies to paper producers through a policy of prohibiting log export that causes Particular Market Situation (PMS). The WTO is a mediator between Indonesia and Australia. The WTO acts as a forum for dispute resolution, there are three results from this study. First, the Dispute Settlement Body states that Australia had violated two articles in the WTO Anti-Dumping agreement and the allegations of Particular Market Situation (PMS) hadn’t been proven. Second, Australia is recommended to adjust the calculation of the amount of margin dumping that has been set on Indonesia's A4 copy paper products since 20 April 2017. Third, the two countries agreed to implement the recommendation within eight months. Keywords: WTO, Dumping, Particular Market Situation, Trade Dispute, Dispute Settlement Body